2D electrolyte
Patent Information
- Application Number
- JP2023535967
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-14
- Filing Date
- 2021-12-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-12-06
Smart Images

Figure 0007638557000002 
Figure 0007638557000003 
Figure 0007638557000004
Abstract
Description
[Technical field]
[0001] The present invention relates to two-dimensional electrolytes and their applications, and to methods for changing the conformation of two-dimensional electrolytes due to changes to the surrounding environment. [Background technology]
[0002] The listing or discussion of a prior document in this specification is not necessarily an admission that the document is part of the state of the art or is common general knowledge. One of the main characteristics of carbon is that there are numerous allotropes with different dimensionality: fullerenes are molecules and therefore zero-dimensional (0D), carbon nanotubes are one-dimensional (1D) structures, graphene is two-dimensional (2D) structures, and graphite and diamond are three-dimensional (3D) structures. The distinct dimensionality of carbon has led to a variety of applications due to the unique functionality of carbon-based materials. Since the isolation of graphene in 2004, the field of 2D materials has developed dramatically due to their special properties and potential for applications in numerous industrial sectors. Unlike common 3D materials, 2D materials have special properties due to their low dimensionality and share characteristics of "soft" and "hard" materials. In 2D materials, electronic (hard) properties can be controlled by conformation (soft properties), leading to a complex interplay between structure and functionality (VM Pereira & AH Castro Neto, Phys. Rev. Lett. 2009, 103, 046801). However, their role as intelligent materials that can undergo reversible dimensional transformations as a result of external stimuli response has been less explored. Reversible morphological control of structures is an important mechanism to tune materials properties (Y. Xia et al., Adv. Mater. 2003, 15, 353-389 and Y. Zhang et al., Nat. Commun. 2015, 6, 6165). These systems are of great relevance for several applications, including drug delivery, hydrogen storage, sensors, membranes for filtration, and structures that mimic biological systems. For example, in polyelectrolyte suspensions, electrostatic interactions are the origin of their response to temperature and pH changes, and their delicate balance is responsible for the reversible morphological transition from molecular chains (1D) to spherical objects (0D) (M. Muthukumar, Macromolecules 2017, 50, 9528-9560; and T. Zhu et al., Nat. Commun. 2018, 9, 4329).Such a reduction in dimensionality is a universal phenomenon, since Coulombic and elastic forces tend to increase the dimensionality, while van der Waals forces tend to decrease it (see, for example, Figure 1). From a physical and chemical point of view, the electrical repulsion between surface charges in 2D materials results in a flat conformation. By changing the amount of charge in the dispersion, the surface charge density of the 2D material can be electrically screened, and its elasticity allows the 2D material to undergo conformational changes by forming different morphologies, the most stable of which are 1D-like structures, i.e. scrolls. Among the numerous strategies to generate scrolls from 2D materials, shock cooling with liquid nitrogen followed by freeze-drying or lyophilisation is one of the most popular methods for preparing graphene oxide (GO) scrolls (T. Fan et al., Nanoscale Res. Lett. 2015, 10, 1-8; and L. Gao et al., RSC Adv. 2018, 8, 19164-19170). Other strategies to fabricate scrolls include high shear stress in a vortex fluid under laser irradiation (TMD Alharbi et al., Carbon NY 2018, 137, 419-424), and the Langmuir-Blodgett (LB) method (Y. Gao et al., Carbon NY 2010, 48, 4475-4482). However, reversible morphology transitions of functionalized 2D materials as a function of changes in external conditions have not been reported so far.
[0003] There is therefore a need to discover new classes of charged 2D materials that can undergo reversible morphological transformations as a result of changes to environmental conditions. Summary of the Invention
[0004] In a first aspect of the present invention, a method of altering the conformation of a nanomaterial electrolyte is provided, comprising: The method includes the following steps: (a) providing a nanomaterial electrolyte in an aqueous medium to provide a mixture having a first state; and (b) subjecting the mixture to one or more of changes in pH, ionic strength, temperature, pressure, sonication, and light to provide a mixture in a second state; The first state of the mixture corresponds to the nanomaterial electrolyte being primarily in a planar two-dimensional conformation or a scrolled one-dimensional conformation; and the second state of the mixture corresponds to the nanomaterial electrolyte being predominantly in an opposite conformation to the first state, i.e., if the nanomaterial electrolyte is predominantly in a flat two-dimensional conformation in the first state, it is predominantly in a scrolled one-dimensional conformation in the second state, or vice versa; The nanomaterial electrolyte comprises a modified two-dimensional nanomaterial having a surface; The surface is modified with a plurality of functional groups on the surface of the modified two-dimensional nanomaterial, the functional groups being selected from one or more of the group consisting of imine, sulfonic acid, sulfonamide, or more specifically amine, hydroxyl, carboxylic acid, thiol, and amide; The nanomaterial electrolyte can reversibly adopt a flat 2D conformation or a scrolled 1D conformation in response to changes in its surrounding environment; The change in the surrounding environment is due to a change in one or more of pH, ionic strength, temperature, pressure, sonication, and light in the surrounding environment; and The amount of said functional groups is greater than that present in the unmodified form of the same two-dimensional nanomaterial.
[0005] In a second aspect of the present invention, a nanomaterial electrolyte is provided, The nanomaterial electrolyte comprises a modified two-dimensional nanomaterial having a surface; the surface is modified with a plurality of functional groups selected from one or more of the group consisting of imine, sulfonic acid, sulfonamide, or more specifically amine, hydroxyl, carboxylic acid, thiol, and amide on the surface of the modified two-dimensional nanomaterial; The nanomaterial electrolyte can reversibly adopt a flat 2D conformation or a scrolled 1D conformation in response to changes in its surrounding environment; The change in the surrounding environment is due to a change in one or more of pH, ionic strength, temperature, pressure, sonication, and light in the surrounding environment; and The amount of said functional groups is greater than that present in the unmodified form of the same two-dimensional nanomaterial.
[0006] In a third aspect of the present invention, there is provided a method of forming a nanomaterial electrolyte as described in the second aspect of the present invention, comprising the steps of: The method includes the following steps: (i) providing an unmodified two-dimensional nanomaterial; and (ii) reacting said unmodified two-dimensional nanomaterial with one or more functionalizing reagents in the presence of a solvent to provide a nanomaterial electrolyte; In a fourth aspect of the present invention, there is provided a drug delivery device comprising: The drug delivery device comprises: a nanomaterial electrolyte according to the second aspect of the present invention; and a drug bound to a surface of the nanomaterial electrolyte; The nanomaterial electrolyte is provided in a scrolled one-dimensional conformation such that the drug is encapsulated within the scrolled one-dimensional conformation and is released when the nanomaterial electrolyte adopts a flat two-dimensional conformation upon exposure to an acidic or basic environment. [Brief description of the drawings]
[0007] [Figure 1]Illustrated morphology transitions of 2D electrolytes and polyelectrolytes in dispersions: (a) 2D electrolyte changes from a flat 2D (top) configuration to a scroll-like 1D (bottom) configuration in dispersion under pH change; and (b) the equivalent diagram in solution of polyelectrolyte, in which the 1D molecular chains change to 0D globular structures. [Diagram 2] A schematic diagram of a typical 2D morphological transition process is shown. [Diagram 3] Figure 1 illustrates the characterisation of different 2D electrolytes: (ab) optical images of a dispersion with reduced functionalised graphene oxide (rGO-SH-FITC) at pH 3.0, where a flat 2D structure is observed; (cd) the same material in a dispersion at pH 9.0, where scrolls are visible; (e) functionalised graphene (G-COOH) scrolls; (f) HR-STEM image with its interlayer distance; and AFM images and respective height profiles of rGO-SH-FITC at (g,j) pH 3.0 (flat); and (h,i,k,l) pH 9.0 (scrolls). [Figure 4] Illustrating the parameterization of the scroll using the geometry of the Archimedean spiral and the optimized structure of a (10,5)-scroll: (a) the parameterization chosen as d is the interlayer distance (measured from HR-STEM images), initial φ0, final φ angle implies inner and outer radii rin = r(φ = φ0), rout = r(φ) (also obtained from microscopy images); (b) a complete scroll; and (c) a scroll with oxygen in the interlayer space. [Diagram 5] Illustrating the effect of ultrasonication on the scrolling mechanism of 2D electrolyte at pH 4.5: (a) scanning electron microscope (SEM) images of graphene oxide (GO) with and without ultrasonication; and (b) HR-STEM images of G-COOH with and without ultrasonication (light grey structures correspond to the lacy carbon support film on the TEM grid). [Figure 6]SEM images illustrating the morphological organization as a function of pH for various 2D electrolytes: (a) GO; (b) rGO-SH; (c) rGO-SH-FITC; and (d) G-COOH. The pH of all samples was adjusted using HCl and KOH under ultrasonication. [Figure 7] AFM images of the morphological transition of GO at various pH are illustrated along with the respective height profiles: (a,b) GO at pH 4.5 (original, 2D flat); (c-e) pH 6.0 (1D scroll); and (f,g) pH 4.5 after readjustment from pH 3.0 (1D scroll) to pH 4.5 (2D flat). [Figure 8] Characterization of various 2D electrolytes is illustrated: (a) high-resolution C1s X-ray photoelectron spectroscopy (XPS) spectra of GO, GO-SH, and rGO-SH; (b) high-resolution S2p XPS spectrum of rGO-SH; (c) zeta potential as a function of pH; (d) Raman spectra showing a slight increase in the relative intensity of the D band of GO after functionalization (GO-SH) and hydrothermal reduction (rGO-SH); (e) zeta potential as a function of pH of rGO-SH and rGO-SH-FITC; and (f) FTIR spectra of GO-SH, rGO-SH, FITC, and rGO-SH-FITC. The dashed ellipse highlights the S=C=N bond in the FITC spectrum. [Figure 9] Optical images of FITC control and rGO-SH-FITC (2D electrolyte) are illustrated: (a) at pH 3.0, 2D planar sheets are observed; and (b) at pH 9.0, 1D scroll structures are observed in 2D electrolyte. [Figure 10] Characterization of graphene and G-COOH is illustrated: (a) Raman spectra of graphene and G-COOH; (b) HR-STEM image of the 2D flat structure; high-resolution (c) C1s; and (d) N1s spectra of graphene and G-COOH. [Figure 11]2D electrolytes in aqueous dispersions: (a) G-COOH; and (b) phase diagrams of rGO-SH are shown. The experimental points of ζ potential vs. pH are indicated by squares (2D flat) and circles (1D scroll) according to the morphological state. The theoretical instability regions at a given average flake size (0.48 μM and 2.33 μM for G-COOH and rGO-SH, respectively) are indicated by shading. The bending rigidity is 0.025 eV for the soft GO-like material (P. Poulin et al., Proc. Natl. Acad. Sci. U. S. A. 2016, 113, 11088-11093). The Hamaker constant is 0.624 eV for the graphene-like material (R. R. Dagastine, D. C. Prieve & L. R. White, J. Colloid Interface Sci. 2002, 249, 78-83), but is very large for r-GO-SH at pH > 7 to mimic the strong covalent S-S bonds formed under alkaline conditions. [Figure 12] SEM images of various types of 2D electrolyte morphologies identified in dispersions at various pHs, and their approximate mean aspect ratios (r) are illustrated: (a) 2D planar isolated sheets, 1 < r < 3; (b) 2D planar aggregated sheets, 1 < r < 3; (c) 2D folded sheets (see arrows), 3 < r < 5; (d) isolated 1D scrolls, formed by a single flake, 5 < r < 15; and (e) twisted 1D scrolls, formed by multiple aggregated flakes, 6 < r < 20. [Figure 13] Statistical analysis of 2D electrolytes: (a) GO, (b) rGO-SH, and (c) G-COOH at various pHs are illustrated together with the distribution curves of their respective aspect ratios (r = length / width). This figure is fitted by a lognormal distribution given by F(r)=[C / σr(2π)1 / 2]exp[-(ln r / rM)2 / 2σ2], where r is the aspect ratio with rM as the median, and C, σ are the fitting parameters. [Figure 14]Statistical analysis at pH 4.5 and distribution of GO morphologies at various pH are illustrated: (a) size distribution curve of aspect ratio of GO at pH 4.5 without ultrasonication, where planar sheets were mainly observed; and (b) distribution of morphologies at various pH based on statistical analysis. [Figure 15] Illustrating the reversibility of the morphology transition: Representative SEM images of GO at pH 3.0 and after readjustment to pH 4.5. [Figure 16] Statistical analysis of the 2D electrolytes (rGO-SH and G-COOH) is illustrated: (a) the average aspect ratio as a function of pH for rGO-SH, showing a tendency to form scrolls with increasing pH. The dots indicate the values achieved after pH readjustment from pH 10.2 to 3.1; (b) statistical distribution of the morphologies of rGO-SH (scrolls (including both twisted and isolated structures), folded, and planar) identified in the samples of various pH; (c) SEM images showing the reversible effect of rGO-SH from 1D scroll structures at pH 10.2 to 2D flat sheets at pH 3.1, respectively; (d) the average aspect ratio showing an increase in 2D flat structures with increasing pH; (e) statistical distribution of structures of G-COOH; (f) HR-STEM images showing the reversible process of G-COOH; and (g) the zeta potential of functionalized graphene (G-COOH) as a function of pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In a first aspect of the present invention, a nanomaterial electrolyte is provided, The nanomaterial electrolyte comprises a modified two-dimensional nanomaterial having a surface; the surface is modified with a plurality of functional groups selected from one or more of the group consisting of imine, sulfonic acid, sulfonamide, or more specifically amine, hydroxyl, carboxylic acid, thiol, and amide on the surface of the modified two-dimensional nanomaterial; The nanomaterial electrolyte can reversibly adopt a flat 2D conformation or a scrolled 1D conformation in response to changes in its surrounding environment; The change in the surrounding environment is due to a change in one or more of pH, ionic strength, temperature, pressure, sonication, and light in the surrounding environment; and The amount of said functional groups is greater than that present in the unmodified form of the same two-dimensional nanomaterial.
[0009] In embodiments herein, the word "comprising" may be interpreted to require the recited features but not to limit the presence of other features. Alternatively, the word "comprising" may also relate to a situation in which only the recited components / features are intended to be present (e.g., the word "comprising" may be replaced by the phrase "consists of" or "consists essentially of"). It is expressly intended that both the broader and narrower interpretations may apply to all aspects and embodiments of the present invention. In other words, the word "comprising" and its synonyms may be replaced by the phrase "consisting of" or the phrase "essentially consisting of" or their synonyms, and vice versa. The phrase "consisting essentially of" and its synonyms may be interpreted herein to refer to a material in which minor impurities may be present. For example, the material may be 90% or more pure, such as greater than 95% pure, such as greater than 97% pure, such as greater than 99% pure, such as greater than 99.9% pure, such as greater than 99.99% pure, such as greater than 99.999% pure, such as 100% pure. As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly indicates otherwise. Thus, for example, reference to "a composition" includes mixtures of two or more such compositions, and the like.
[0010] As used herein, the term "two-dimensional nanomaterial" refers to a material having an atomic thickness of up to 10 layers and other dimensions at the nano- or microscale. As used herein, the term "modified two-dimensional nanomaterial" refers to a two-dimensional nanomaterial that has been altered through the addition and / or substitution of functional groups. This can be either by the addition of functional groups to a material that is essentially devoid of functional groups (e.g., graphene), or by the addition and / or alteration of functional groups that were present in the material. As an example of the latter, unmodified graphene oxide can contain epoxides, alcohols, and carboxylic acids. Through the chemistry disclosed herein, the epoxides may be ring-opened by the addition of additional molecules, thereby increasing the amount of hydroxyl groups and also introducing additional functional groups (e.g., amino groups) on the surface of the material.
[0011] In certain embodiments, the number of functional groups present in the modified material pre-functionalized may increase. This may be measured and quantified by any suitable method. For example, the functional groups may be verified and quantified by X-ray photoelectron spectroscopy (XPS) by calculating the atomic percentage of the elements to identify the type of functional group in each sample of material (e.g., before and after modification). By considering the relative peaks of each element, a quantification report is provided that includes the atomic percentage of the element. The degree of functionalization will depend on the type of functional group and the reaction carried out. For example, in the case of graphene oxide functionalized with SH, a high-resolution C1 spectrum will show deconvoluted peaks due to C-Si and CS, and originating from the molecule used for functionalization (e.g., 3-mercaptopropyltrimethoxysilane). From this spectrum and the spectrum of unfunctionalized graphene oxide before functionalization, it is possible to make an estimate of the functionalization, which may indicate an overall increase in the number of functional groups present on the two-dimensional material. Other techniques such as infrared and Raman spectroscopy may also be used qualitatively in this investigation.
[0012] As can be seen, the nanomaterial electrolyte can be provided as a material per se, or as an electrolyte formulation in a suitable medium, such as an aqueous environment. This aqueous environment can allow the nanomaterial electrolyte to undergo a change in its form due to a change in the surrounding environment, such as a change in pH. As can be seen, the functional groups can be selected from one or more of the group consisting of imine, sulfonic acid, sulfonamide, or more specifically amine, hydroxyl, carboxylic acid, thiol, and amide, while these groups can be present in ionic (e.g., ammonium, carboxylic acid) or free base / free acid form depending on the pH (or other environmental conditions) to which they are exposed. Thus, in embodiments of the invention that can be mentioned herein, the change in the surrounding environment can be due to a change in one or more of temperature, salt concentration, pH, ionic strength, and ultrasonic treatment in the surrounding environment. In specific embodiments that can be mentioned herein, the change in the surrounding environment can be due to a change in one or more of pH, ionic strength, and ultrasonic treatment in the surrounding environment; or one or both of pH and ultrasonic treatment in the surrounding environment.
[0013] As shown in the examples below, a change in pH may change the charge on the surface of the two-dimensional electrolytes disclosed herein, and a change in one direction (higher or lower pH) may lead to the material adopting a substantially flat conformation, while a change in a second direction may result in the material adopting a substantially scrolled conformation. As used herein, the term "substantially X conformation" may refer to a material in which at least 55%, such as 65%, such as 70%, such as 75%, such as 80%, such as 85%, such as 90%, such as 95%, such as 99%, such as 99.99%, such as 100% of the material adopts conformation X. In certain embodiments, when pH is used to control the conformation, it may be necessary to supply additional energy to the system to enable the conformational change (e.g., the transition to scrolls may be energetically unfavorable due to increased elastic energy). This may be achieved by any suitable method, such as the use of changes in temperature, centrifugation, and light irradiation, or more specifically, sonication. It will be appreciated that not all two-dimensional electrolytes adopt either a flat or a scrolled conformation: some of the two-dimensional electrolytes may adopt a folded conformation, partly flat and partly folded, as discussed in the Examples section below.
[0014] The modified two-dimensional nanomaterial used in the embodiments herein may be any suitable two-dimensional nanomaterial that has the ability to accept functionalization of its surface. Examples of suitable two-dimensional nanomaterials include, but are not limited to, graphene, graphene oxide, reduced graphene oxide, hexagonal boron nitride, transition metal dichalcogenides, and combinations thereof. In specific embodiments that may be mentioned herein, the modified two-dimensional nanomaterial may be selected from the following: one or more of graphene, graphene oxide, and transition metal dichalcogenides (e.g., molybdenum disulfide); one or more of graphene and graphene oxide; transition metal dichalcogenides (e.g., molybdenum disulfide). In embodiments of the present invention that may be mentioned herein, the modified two-dimensional nanomaterial may be a single layer or formed from 2 to 5 layers.
[0015] The multiple functional groups may be selected from any combination of such groups mentioned herein. Indeed, it is possible that two or more functional groups may be present on the same binding moiety (e.g., an amine functional group and a carboxylic acid may be present on an amino acid moiety, such as a cysteine-functionalized graphene surface, where a thiol group forms a covalent bond to the graphene surface). For example, the multiple functional groups may be selected from one or more of the group consisting of: (a) amine, hydroxyl, carboxylic acid, thiol, and amide; or (b) amino, hydroxyl, carboxylic acid, and thiol; or (c) hydroxyl, carboxylic acid, and thiol; or (d) carboxylic acid and thiol; or (e) amine and imine; or (f) hydroxyl, carboxylic acid and sulfonic acid; or (h) thiol and sulfonamide; or (h) amine and carboxylic acid. Without wishing to be bound by theory, it is believed that the multiple functional groups introduced into the modified 2D nanomaterials allow the morphological behavior of the nanomaterial to be tailored to suit any particular use, for example, by tailoring it to respond to a specific set of ambient environmental conditions, as discussed herein.
[0016] In certain embodiments, the described electrolytes may be coated with additional materials to provide additional functionality. For example, the electrolyte may be coated with a material selected from one or more of the group consisting of polymers, proteins, carbohydrates, and nanoparticles, and the nanomaterial electrolyte may be coated with a material selected from one or more of the group consisting of poly(ethylene glycol) (PEG), poly(methyl methacrylate) (PMMA), proteins, silica, dextran, gold nanoparticles, gold nanorods, silver nanoparticles, platinum nanoparticles, titanium dioxide, and silica nanoparticles. This additional coating may be physically or covalently associated with the 2D electrolyte structure. In some embodiments, these coatings may be useful for protecting the 2D electrolyte structure during device fabrication. Some of these coatings may also be interesting for biomedical applications, as they may exhibit reduced toxicity or extended circulation lifetime, such as PEG, proteins, and silica. In some embodiments, these additional coatings may be useful for energy applications such as solar cells and electrochemistry. For example, metal nanoparticle coatings may absorb light and, due to local surface plasmon resonance, cause local heating effects and induce morphological transitions in the 2D electrolyte. Additionally or alternatively, the nanomaterial electrolyte may incorporate fluorescent groups covalently attached to the surface. The functionalizing agent may be a fluorescent molecule, and a change in conditions may also result in a change in molecular emission. This may be particularly useful for detection and sensor applications.
[0017] The nanomaterial electrolytes disclosed herein are particularly useful due to their ability to change conformation when the environment of the surrounding environment changes. Thus, in a further aspect of the present invention, a method for changing the conformation of the nanomaterial electrolyte as described herein above is disclosed, the method comprising the steps of: (a) providing the nanomaterial electrolyte in an aqueous medium to provide a mixture having a first state; and (b) subjecting the mixture to one or more of the following changes: pH, ionic strength, temperature, pressure, sonication, and light to provide a mixture in a second state; the first state of the mixture corresponds to the nanomaterial electrolyte being predominantly in a flat two-dimensional conformation or a scrolled one-dimensional conformation; and the second state of the mixture corresponds to the nanomaterial electrolyte being predominantly in the opposite conformation to the first state, i.e., if the nanomaterial electrolyte is predominantly in a flat two-dimensional conformation in the first state, it is predominantly in a scrolled one-dimensional conformation in the second state, or vice versa. The material can be reversibly interconverted from a flat conformation to a scrolled conformation in response to changes in environmental conditions. Thus, the method may further comprise the step of: (c) subjecting the mixture to one or more of the following changes in the surrounding environment: pH, ionic strength, temperature, pressure, sonication, and light to return the mixture to the first state, i.e., to cause the nanomaterial electrolyte to return to the morphology in the first state.
[0018] An advantage associated with the currently disclosed method is that it does not require large temperature changes or the use of solvents to effect the reversible morphological transition. In addition, the process of conformational shift is environmentally friendly since it can be carried out in an aqueous environment, which also increases the potential applications in which the electrolyte can be used. Furthermore, the method is simple, versatile, template-free and solvent-free, and reversible, which allows for applications in many fields, such as smart responsive materials (e.g., drug delivery systems), batteries, and sensors. As can be seen, any suitable change in the surrounding environment can enable the conformational change. For example, the change can be one or more of temperature, salt concentration, pH, ionic strength, and sonication in the surrounding environment, and the change can be one or both of pH and sonication in the surrounding environment. More specifically, the change in the surrounding environment can be due to the following changes: one or more of pH, ionic strength, and sonication in the surrounding environment; or one or both of pH and sonication in the surrounding environment.
[0019] As can be seen, the nanomaterial electrolyte used in the present method is the same as that described hereinabove, and therefore, for the sake of brevity, a discussion of possible variations in this material will not be repeated.
[0020] In a further aspect of the present invention, there is disclosed a method of forming a nanomaterial electrolyte as hereinbefore described, comprising the steps of: (i) providing an unmodified two-dimensional nanomaterial; and (ii) reacting the unmodified two-dimensional nanomaterial with one or more functionalizing reagents in the presence of a solvent to provide a nanomaterial electrolyte.
[0021] The unmodified two-dimensional nanomaterial may be selected from any suitable material. Examples of suitable unmodified two-dimensional nanomaterials include, but are not limited to, graphene, graphene oxide, reduced graphene oxide, hexagonal boron nitride, and transition metal dichalcogenides. In a specific embodiment, the unmodified two-dimensional nanomaterial is selected from one or more of graphene, graphene oxide, and transition metal dichalcogenides (e.g., molybdenum disulfide). More specifically, the unmodified two-dimensional nanomaterial may be selected from one or more of graphene and graphene oxide. Alternatively, the unmodified two-dimensional nanomaterial may be a transition metal dichalcogenide (e.g., molybdenum disulfide). In an embodiment of the invention that may be mentioned herein, the unmodified two-dimensional nanomaterial is a single layer or is formed from 2 to 5 layers.
[0022] The functionalizing agent can be any bifunctional (or trifunctional, tetrafunctional, etc.) molecule that can be attached to the surface of the 2D material by one of the functional groups and has at least one other functional group that responds to an environmental change (such as pH). For all types of 2D electrolytes mentioned herein, the functionalizing agent can be multiple types of molecules. Linkers can be selected to expand the types of molecules / groups and functional groups. For graphene oxide, for example, the functionalizing agent can be any bifunctional (or trifunctional, etc.) molecule that can be attached to the graphene oxide (GO) surface and has functional groups that can be protonated or deprotonated under certain circumstances. The molecules can be attached through epoxy or hydroxyl groups on the GO. Examples include, but are not limited to, aminosilanes, carboxylsilanes, thiolsilanes, such as (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-mercaptopropyl)methyldimethoxysilane, etc. Functionalization with silane molecules is also called silanization. GO functionalizing agents can also be nucleophiles that bind to epoxy or carboxyl functional groups on the GO surface. In this case, amination or esterification can be performed. Examples include, but are not limited to, bifunctional or multifunctional amines such as ethylenediamine (EA), 1,6-hexanediamine (HA), triethylenetetramine (TETA), etc. In some embodiments, some intermediate molecules can be used to activate the functional groups and improve the yield of the reaction. Examples include 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), N-hydroxysuccinimide (NHS), or thionyl chloride SOCl. 2 GO functionalization can be combined with the reduction of GO molecules to minimize the interference of residual groups on the GO surface during the scrolling / unscrolling process. Reduction can be performed thermally by temperature-controlled treatment or chemically using reducing agents such as ascorbic acid, hydrazine, or sodium borohydride. The functionalization of pristine graphene involves the sp 2The molecule can be any molecule that attacks the carbon atom. The reaction can be carried out in an organic solvent such as DMF, DMSO, NMP, DMSO, etc., using a diazonium salt and an azide molecule. Examples of molecules include any azide compound (e.g., azido-OH, azido-COOH, azido-NH), such as 5-azidopentanoic acid, azido-dPEG-amine, azido-dPEG-acid, 3-azido-1-propanol, 3-azido-1-propanamine, etc. 2 Examples include, but are not limited to, dienophiles (e.g., azide polymers). The functionalizing agent for pristine graphene can also be a dienophile. Examples include, but are not limited to, azomethine ylides that undergo 1,3-dipolar cycloaddition reactions in organic solvents such as DMF.
[0023] Other non-limiting examples of two-dimensional electrolytes include single-layer or few-layer transition metal dichalcogenides, such as MoS 2 can be functionalized with functional groups at the sulfur vacancies or by utilizing negative charges at the 1T phase. In the first case, bifunctional molecules containing thiol groups can be used. Examples include, but are not limited to, lipoic acid (LA) and derivatives, mercaptopropionic acid (MPA), thioglycerol (TG), cysteine. In the second case, electrophiles such as iodoacetamide can be used.
[0024] Thus, more generally, the functionalizing reagent(s) may be selected from compounds that provide the nanomaterial electrolyte with one or more functional groups selected from the group consisting of imines, sulfonic acids, sulfonamides, or more specifically, amines, hydroxyls, carboxylic acids, thiols, and amides. Examples of these include the following sets, which may include sets of functional groups that may be introduced together. For example, the functionalizing reagent(s) may be selected from compounds that provide the nanomaterial electrolyte with one or more functional groups selected from one or more of the following groups: (a) amines, hydroxyls, carboxylic acids, thiols, and amides; (b) aminos, hydroxyls, carboxylic acids, and thiols; (c) hydroxyls, carboxylic acids, and thiols; (d) carboxylic acids and thiols; (e) amines and imines; (f) hydroxyls, carboxylic acids, and sulfonic acids; (g) thiols and sulfonamides; and (h) amines and carboxylic acids (e.g., amino acids).
[0025] In a specific embodiment, the one or more functionalizing reagents may be selected from one or more of the group consisting of thioamines, bifunctional sulfonic acids, aminosilanes, carboxylsilanes, thiolsilanes, bifunctional amines, polyfunctional amines, azide compounds, dienophiles, thioacids, and haloacetamides. More specifically, the one or more functionalizing reagents may be selected from one or more of the group consisting of sulfanilic acid, (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-mercaptopropyl)methyldimethoxysilane, ethylenediamine (EA), 1,6-hexanediamine (HA), triethylenetetramine (TETA), azido-OH, azido-COOH, azido-NH 2, azido polymers, lipoic acid (LA), lipoic acid derivatives, mercaptopropionic acid (MPA), thioglycerol (TG), cysteine, methyl iodide, and iodoacetamide. More specifically, the one or more functionalizing reagents may be selected from one or more of the group consisting of (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-mercaptopropyl)methyldimethoxysilane, ethylenediamine (EA), 1,6-hexanediamine (HA), triethylenetetramine (TETA), 5-azidopentanoic acid, azido-dPEG-amine, azido-dPEG-acid, 3-azido-1-propanol, 3-azido-1-propanamine, azomethine ylide, lipoic acid (LA), lipoic acid derivatives, mercaptopropionic acid (MPA), thioglycerol (TG), cysteine, methyl iodide, and iodoacetamide.
[0026] As described above, step (ii) of the method includes the step of reacting an activating molecule (e.g., the activating molecule is selected from the group consisting of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), N-hydroxysuccinimide (NHS), and thionyl chloride, SOCl). 2 In some embodiments, the reaction product of step (ii) of the method may be subjected to reduction in step (iii), the reducing step comprising reacting the reaction product of step (ii) with a reducing agent in the presence of a solvent (e.g., the reduction may be performed using a reducing agent selected from one or more of the group consisting of ascorbic acid, hydrazine, and sodium borohydride). In some embodiments, the reaction product of step (ii) of the method may be subjected to reaction with a fluorescent agent in step (iv) in the presence of a solvent (e.g., the fluorescent agent may be fluorescin isothiocyanate isomer type I, and the reaction product of step (ii) may comprise a thiol functional group).
[0027] In a further aspect of the present invention, a drug delivery device is disclosed comprising: a nanomaterial electrolyte as hereinbefore described; and a drug bound to a surface of said nanomaterial electrolyte; said nanomaterial electrolyte being provided in a scrolled one-dimensional conformation such that said drug is encapsulated within said scrolled one-dimensional conformation and is released upon exposure to an acidic or basic environment, when said nanomaterial electrolyte adopts a flat two-dimensional conformation. EXAMPLES
[0028] [material] Graphene oxide (GO;H 2 Graphene flakes (XP grade powder) were purchased from 2D Materials Pte. Ltd.
[0029] [Analysis technology] The sample suspension was deposited on silicon (Si) substrates for XPS and SEM analysis, and on Si substrates with 300 nm silicon dioxide (Si / SiO 2 ) was drop cast on.
[0030] [XPS] XPS measurements were performed using a Kratos AXIS Ultra DLD (Kratos Analytical Ltd) and the dispersion was drop cast onto a Si substrate. All spectra were calibrated using the Si peak from the substrate (99.4 eV). Shirley-type background, peak fitting, and quantification were analyzed by CasaXPS software (version 2.1.19), where the C1s spectrum was deconvoluted to the asymmetric graphite peak (~284.5 eV) and the remaining peaks were fitted using a Gaussian-Lorentzian GL(30) lineshape.
[0031] [AFM] AFM measurements were performed on a Bruker Dimension Icon Microscope (Bruker Corporation, Billerica, Massachusetts, USA) operated under ambient conditions with ScanAsyst tapping mode and 512 scan lines.
[0032] [Optical microscope] 25 μL of thiolate GO (rGO-SH) (0.01 mg / mL) was deposited on a pre-cleaned glass slide. The dispersion was surrounded by a thin well of parafilm with an opening of 8 mm × 8 mm. A pre-cleaned coverslip was then used to cover both the droplet and the parafilm. The coverslip prevents the formation of a meniscus and reduces the evaporation rate of the solution. Finally, the edges were sealed with epoxy glue. Further characterization was performed under bright field mode using a 100x immersion lens on an upright fluorescence microscope.
[0033] [Fourier transform infrared spectroscopy (FTIR)] An ALPHA Platinum-ATR (Bruker Corporation, Billerica, MA, USA) instrument was used. For this, an aqueous suspension of GO was freeze-dried and prepared by the KBr disk method, and spectra were acquired in attenuated total reflectance (ATR) mode.
[0034] [Raman spectroscopy] Raman spectroscopy was performed on a WITec Alpha 300R (WITec Wissenschaftliche Instrumente und Technologie GmbH, Germany) with an excitation wavelength of 532 nm and a 100x objective.
[0035] [SEM] SEM was performed on Lacey carbon-gold transmission electron microscope (TEM) grids (TedPella) using an FEI Verios 460 L FESEM (FEI Company, Hillsboro, OR, USA).
[0036] [High-resolution scanning transmission electron microscopy (HR-STEM)] HR-STEM analysis was performed on Lacey carbon-gold transmission electron microscope (TEM) grids (TedPella) using a JEOL JEM-ARM200F (JEOL Ltd., Akishima, Japan) atomic resolution analytical electron microscope.
[0037] Example 1. Synthesis of 2D electrolyte 2D electrolytes have been synthesized using organic molecules as reactive species to add various functionalities to GO and graphene by covalent modification. The functionalization route described below is just one example among many.
[0038] [GO-SH and rGO-SH] First, GO was dispersed in ethanol (1 mg / mL) by centrifugation. Then, 5 μL of (3-mercaptopropyl)trimethoxysilane was added to 5 mL of the GO dispersion. The dispersion was kept under stirring at room temperature for 24 h, and then centrifuged twice in ethanol and once in deionized water (DI water) to remove the residues of silane molecules to obtain GO-SH. After functionalization (GO-SH), a mild hydrothermal reduction was performed to remove some of the COOH groups from the edges to obtain a much more controlled chemical surface to induce the scrolling mechanism. The reaction was carried out by adding ascorbic acid (7.5 mg) to the GO suspension (15 mL) under stirring and N 2 After 15 min, the temperature was increased to about 60 °C for 50 min. Finally, the system was washed with DI water to obtain rGO-SH.
[0039] [rGO-SH-FITC] Fluorescein isothiocyanate isomer type I (FITC) was used without further purification. For functionalization, FITC was first dissolved in anhydrous DMSO at 1 mg / mL. Then, 1 mL of this FITC solution was added to 30 mL of rGO-SH (0.2 mg / mL, pH = 6–7). The system was kept under stirring at room temperature for 6 h, and finally, dialyzed against ultrapure water to remove excess FITC. As a control, FITC solutions at pH 3.0 and 9.0 were also prepared on Si / SiO 2 (300 nm thick) substrates and were evidently free of any significant structures. The insertion of fluorescent molecules onto the graphene surface can open up new applications, for example in the biomedical field, demonstrating the multifunctionality of these materials.
[0040] [G-COOH] Graphene is a cationically bonded azide (N 3 - Through decomposition of the N-(2-azide) group, the compound was functionalized with 5-azidopentanoic acid (Figure 2). Upon thermal activation, the N 2 The release of nitrene (RN) and the addition of nitrene (RN) onto graphene in DMSO allowed the incorporation of the molecule, resulting in graphene functionalized with carboxylic acid (-COOH) (J. Choi et al., J. Phys. Chem. C. 2009, 113, 9433-9435; LH Liu, MM Lerner & M. Yan, Nano Lett. 2010, 10, 3754-3756; and M. Zhao et al., Sci. Rep. 2016, 6, 37112). Typically, the conformation of functionalized graphene, GO sheets, and other 2D materials is tuned by modifying the properties of the medium (pH) and, consequently, the surface charge of graphene (Figure 2). The reaction was carried out as follows: 40 mL of graphene at 0.2 mg / mL in DMSO was mixed with N 2 The reaction was prepared in a round-bottom flask under ambient conditions and sonicated for 15 min at 18 °C. The system was then connected to a condenser and 5-azidopentanoic acid (250 mg) was added under magnetic stirring. The reaction was run at 45 °C under N 2The mixture was kept under ambient atmosphere and stirring for 72 hours. Since the initial bending of the graphene sheets is unfavorable due to the increase in elastic energy, this transition needs to be assisted by sonication. Specifically, the reaction mixture was diluted with ultrapure water and sonicated for 10 minutes at 10°C. During sonication, acid (H 2 SO 4 ) or base (KOH) solution was added to the suspension to reach the desired pH, and the system was sonicated for another 20 min at 10 °C. The time and temperature of sonication may vary depending on the 2D system. The system was then centrifuged and suspended in isopropanol. This process was repeated, followed by washing with water and sonication for 5 min at 10 °C to obtain G-COOH. Graphene showed good stability in water after functionalization.
[0041] Example 2. Characterization of GO, GO-SH, rGO-SH, rGO-SH-FITC, and G-COOH The 2D electrolytes were characterized via optical microscopy to show the morphology transition in the liquid dispersions as a function of pH. A reversible transition from 2D to 1D (flat-like to scroll-like) structure was observed in the dispersions at various pHs (Figure 3a-d). The scrolls were characterized microscopically using HR-STEM (Figure 3e-f) and AFM under dry conditions (Figure 3g-i), including their respective height profiles (Figure 3j-l). The change in morphology was omnipresent in all these characterization techniques. Figure 3e-f shows HR-STEM images of the functionalized graphene, G-COOH, where the scroll structure can be observed along with its layers (Figure 4a). The layered structure of G-COOH can be seen, which is reminiscent of multi-walled carbon nanotubes, both in their original form (J. H. Lehman et al., Carbon NY 2011, 49, 2581-2602) and in their unzipped form (J. Lim et al., Nat. Commun. 2016, 7, 10364; and L. Xue et al., Nat. Commun. 2018, 9, 3819). Thus, the scrolls have an Archimedean spiral structure with an interlayer distance d of 0.43 nm, slightly larger than that of graphite (0.34 nm).
[0042] GO is an amorphous, non-stoichiometric material, hydrophilic, and has acid properties when dispersed in water, with a 2D flat structure. However, after ultrasonication, the formation of scrolls was observed at this particular pH (Fig. 5). The morphology transition of GO under various pH can be observed by SEM (Fig. 6a) and AFM (Fig. 7). Since GO has many oxygenated functional groups on its heterogeneous chemical surface, when ultrasonicated after pH adjustment, we observed 1D scroll morphology by SEM in a wide range of pH values (Fig. 6a), even in extreme cases such as strongly acidic (pH 2.5-3.0) or alkaline (pH 11) dispersions. At intermediate pH values (pH 6), some 1D scroll structures were also observed. In Fig. 6b, we showed that scroll-like structures were mainly formed with increasing pH. The thiol groups can be deprotonated (SH → S) at higher pH. - ), when stimulated by sonication, they internally bonded to form disulfide bonds, resulting in a scroll-like morphology, whereas at low pH a 2D planar structure prevailed. The reversible formation of disulfide bonds is the mechanism used by proteins, which are 1D electrolytes, to maintain their tertiary structure (CS Sevier & CA Kaiser, Nat. Rev. Mol. Cell Biol. 2002, 3, 836-847).
[0043] The GO samples were also characterized via AFM to image and assign the height profiles of GO flat sheets at pH 4.5 (Fig. 7a–b), scroll structures at pH 6.0 (Fig. 7c–e), and GO flat sheets at pH 4.5 after pH readjustment (from pH 3.0 to pH 4.5) (Fig. 7f–g), demonstrating the reversibility of the scrolling mechanism. Unlike previous reports on GO scrolls (Y. Gao et al., Carbon NY 2010, 48, 4475-4482; YK Kim & DH Min, Carbon NY 2010, 48, 4283-4288; RLD Whitby et al., ACS Nano. 2012, 6, 3967-3973; B. Tang et al., Chem. Mater. 2018, 30, 5951-5960; and TMD Alharbi et al., Carbon NY 2018, 137, 419-424), we demonstrate the reversibility and generality of the morphology transition common to any 2D electrolyte.
[0044] XPS characterization of GO, GO-SH, and rGO-SH are shown in Figure 8 and Table 1. The elemental chemical states and the presence of functional groups on GO were investigated by XPS (Figure 8a). After deconvolution of the high-resolution C1s region, five different chemical states can be identified: 284.34 eV (C=C), 285.03 eV (CC), 286.96 eV (CO), 287.41 eV (C=O), and 288.38 eV (OC=O). The high-resolution C1s XPS spectrum in Figure 8a shows that after functionalization, the relative intensity increased in the region related to the bond energies of C-Si and CS, indicating that silane and thiol groups were successfully introduced onto the GO surface (PC Ma, JK Kim & BZ Tang, Carbon NY 2006, 44, 3232-3238). The high-resolution S2p spectrum of rGO-SH also indicates the formation of C-S bonds (Figure 8b). In addition, after reduction, the percentage of oxygenated groups such as C=O (dark green) and OC=O (purple) decreased by about 50% compared to GO-SH due to the removal of COOH groups (Table 1). The color of the resulting rGO-SH was slightly darker than that of GO-SH, thus consistent with reduction.
[0045] JPEG0007638557000001.jpg70166
[0046] The zeta potentials of GO-SH and rGO-SH were measured at various pH values (2–12) to verify the stability of the dispersions and their surface charge densities (Figure 8c). As expected, the pK a At higher pH (pH 4-5), the zeta potential values are slightly less negative. However, the zeta potential values are still highly negative, which makes it difficult to separate the contribution of SH groups. Overall, the pK a The pK of the SH group was about pH 8-9. a is at a basic pH, so as the pH increases, the thiol group is deprotonated (SH→S -), stimulated by sonication, internally combine to form reversible disulfide bonds (CS Sevier & CA Kaiser, Nat. Rev. Mol. Cell Biol. 2002, 3, 836-847), preserving the scroll morphology. Therefore, no significant changes were observed between GO-SH and rGO-SH. The Raman spectrum (Figure 8d) reveals that after functionalization and reduction, the relative intensity of the D band increased slightly. This is expected due to the increase in the number of chemical groups and defects, which results in a change in phonon vibrations after the reaction.
[0047] FTIR was acquired on all Si substrates. Figure 8f compares the spectra of FITC, GO-SH, rGO-SH, and rGO-SH-FITC. It is expected that the isothiocyanate group (S=C=N) is bonded to the thiol (SH) group of rGO-SH. The 2051 cm radiated from the isothiocyanate group S=C=N in the FITC molecule after bond formation. -1 The peak at 300 nm disappeared from the FTIR spectrum, indicating that the covalent binding of FITC molecules with rGO-SH led to the formation of another 2D electrolyte, rGO-SH-FITC. Mild reduction of GO-SH reduces the intensity of the peaks due to the oxygenated groups of rGO-SH. The zeta potential as a function of pH did not show any significant change upon the binding of FITC, indicating that the free thiol groups were still attached to the GO surface and survived the morphology transition (Figure 8e). Furthermore, similar to the case of rGO-SH, 2D flat structures of rGO-SH-FITC were observed at low pH, while 1D scrolls were observed at higher pH values (Figure 6c), indicating that the addition of fluorescein molecules did not impair the pH-responsive ability of the 2D electrolyte to change its morphology. Specifically, 2D flat sheets can be seen at pH 3.0, while 1D scroll structures can be seen at pH 9.0 (Figure 9).
[0048] G-COOH was characterized by Raman, HR-STEM, and XPS (Figure 10). The increase in ID / IG ratio in the Raman spectrum (Figure 10a) indicates evidence of covalent functionalization. The typical lateral dimensions of G-COOH sheets are in the range of 0.5-2 um (Figure 10b). The morphology of G-COOH under various pH was investigated by STEM (Figure 6d). From the original pH (about 6), acid or base was added with the intention of modifying the surface charge of graphene. As the pH decreased, 1D scrolls were observed. At pH 7, 2D flat structures were mainly observed, while below pH 5, folded or partial scroll structures dominated. The darker contrast and reduced lateral dimensions at acidic pH indicate the formation of 1D scroll structures. These results support the phase diagram (Figure 11a). We observed that two main factors are important in scroll formation: (i) dispersion concentration, where at low concentrations (0.04 mg / mL), 1D scroll structures are favored against stacking and aggregation (B. Tang et al., Chem. Mater. 2018, 30, 5951-5960); and (ii) the effect of ultrasonication, which considerably improves the 1D scroll yield (Figure 5). Deconvolution of the high-resolution C1s XPS spectrum of G-COOH shows, besides the asymmetric C=C peak at 284.4 eV, other small peaks attributed to the presence of a few oxygen-containing functional groups (Figure 10c). They are ascribed to hydroxyl (CO) at 285.9 eV, epoxy / ether (COC) at 286.7 eV, carbonyl (C=O) at 287.5 eV, and carboxylic acid (OC=O) at 288.4 eV. The peaks at 291–294 eV are π-π * (V. Datsyuk et al., Carbon NY 2008, 46, 833-840; and H. Estrade-Szwarckopf, Carbon NY 2004, 42, 1713-1721). By comparing the C1s spectra, it was found that after functionalization with 5-azidopentanoic acid, the sp 3A relative increase in bonds and oxygen / nitrogen groups can be observed, supporting evidence of surface modification. The high-resolution N1s spectrum after the first step of functionalization (Figure 10d) can be resolved into two peaks at 400.3 eV and 401.3 eV. These energies correspond to the azide groups (N - =N + =N - ), characteristic of tertiary amines and amides, and not N 2 This is consistent with the removal of cations and their attachment to the graphene surface (PC Ma et al., Carbon NY 2010, 48, 1824-1834).
[0049] Example 3. Statistical Analysis Due to the size and thickness distribution of the 2D material flakes used in this study, the morphology transitions are statistical in nature, so the information collected by SEM and STEM was also used to interpret the results by statistical means. Statistical analysis was used to estimate the percentage of 1D scrolls formed in the suspension as a function of pH. Dispersions of various pH were drop-cast onto suitable substrates (silicon for GO and its functionalized forms, and TEM grids for G-COOH) and at least 100 structures were imaged to obtain their lateral dimensions (length L (defined as the largest dimension) and width W). In addition to the percentage of 1D scrolls, we also identified other morphological configurations. The observed structures were further classified according to their morphology into planar, folded, scrolled and isolated, or scrolled and twisted (Figure 12). Thus, the number of counts based on multiple structures as a function of aspect ratio (r = L / W ≥ l) was given in the size distribution chart in Figure 13.
[0050] [Results and Discussion] From statistical analysis, we showed that GO forms scrolls over a wide pH range (from the lowest to the highest pH observed), which is mainly due to the heterogeneity of the chemical surface of this material (Figure 13). In GO (Figure 13a) and rGO-SH (Figure 13b) dispersions, the average aspect ratio changed with pH, as both the length and width of the scrolls depended on the pH. The varying length indicates that the size of the samples was also different in each dispersion prepared at various pHs. In G-COOH dispersions (Figure 13c), the aspect ratio changed mainly due to the width, whose median value rapidly decreased with pH and saturated at about 120 nm in acidic solutions. The length remained almost the same in all dispersions studied (median length was about 440 nm). This suggests that the size of the flakes was the same at each pH studied, and therefore the median width could be considered as the median outer scroll diameter. Considering the interlayer distance (d = 0.43 nm), the maximum number of turns of the scroll is N max = D / (2d), the inventors estimated that the maximum number of turns was about 140 (Fig. 3f). 0 ≫2π (Fig. 4a), which was clearly less. Interestingly, GO showed a significant amount of scroll species throughout the entire pH range (Fig. 13a), but the amount of scrolls detected for GO was dramatically reduced under two conditions: (i) without sonication at the original pH of 4.5 (Fig. 14a), and (ii) after pH readjustment from pH 3.0 to 4.5 (pH3.0-4.5R) (Fig. 13a). These results indicate the reversible morphology transition capability of this material (Fig. 15).
[0051] On the other hand, in the anionic 2D electrolyte rGO-SH, where the chemical surface is more controlled, 2D flat sheets were formed mainly at pH 2.9, while 1D scrolls were found mainly at higher pH. The reversibility of this process can be seen in Figure 13a, showing a size distribution analysis varying the pH from 3 to 10 and back. As seen in Figure 16a, the average aspect ratio of the 2D flat sheets was about 2.5. However, as the pH increases into the alkaline region, it can be seen that the average aspect ratio increases significantly to about 7.0, due to the increasing presence of 1D scroll structures. In rGO-SH (Figure 16b), a clear trend emerges, showing an increase in scroll content with increasing pH (from 9.5% of 1D scroll structures at pH 2.9 to 79.4% at pH 10.2), while the amount of 2D flat structures decreases (from 65% of 2D flat structures at pH 2.9 to 1.3% at pH 10.2), and the folded structures decrease as well. In Fig. 16c, we show that the majority of the 1D scroll structures at pH 10.2 unfold at pH 3.1 in response to the external conditions. After pH readjustment, the average aspect ratio decreases to the original ∼2.9 (Fig. 16a), almost the same as that observed for the planar sheets at lower pH values (Fig. 13b). Thus, Fig. 16a and c show the reversibility of this process. The reversible formation of disulfide bonds is an important mechanism used by proteins, a type of polyelectrolyte, to maintain their tertiary structure.
[0052] For G-COOH, we observed the opposite behavior to that seen for rGO-SH, i.e., a decrease in the percentage of scrolls in response to increasing pH (Figure 16d-e). As previously mentioned, these morphological changes can be explained by the modification of the surface charge density of G-COOH. As the pH approaches below the isoelectric point (~4.9), the carboxyl groups become fully protonated, resulting in increased hydrophobicity and resulting in folding, stacking, and precipitation (RLD Whitby et al., ACS Nano. 2012, 6, 3967-3973). At higher pH, the carboxylates (COO) of the carboxylic acids (COOH) are converted to carboxylates (COO -) groups, the negative surface energy increases (ζ potential ≥ -30 mV, Figure 16g), favoring a 2D planar morphology. Accordingly, after pH readjustment from lower to higher pH, a planar structure was observed, demonstrating the reversibility of the scrolling mechanism (Figure 16f). The interplay between extreme pH values indicates the ability of the 2D electrolyte to undergo a reversible morphological transition.
[0053] The opposite responses of the two examples of 2D electrolytes (rGO-SH and G-COOH) highlight the possibility of tuning stimuli-responsive behavior based on the functional groups attached to the 2D material surface. Moreover, because the method is reversible, environmentally friendly, and template- and solvent-free, 2D electrolytes can extend their use to a wide range of applications, from batteries and sensors to drug delivery systems.
Claims
1. 1. A method for altering the conformation of a nanomaterial electrolyte, comprising: The method includes the following steps: (a) providing a nanomaterial electrolyte in an aqueous medium to provide a mixture having a first state; and (b) subjecting the mixture to one or more of changes in pH, ionic strength, and sonication to provide a mixture in a second state; the first state of the mixture corresponds to the nanomaterial electrolyte being primarily in a planar two-dimensional conformation or a scrolled one-dimensional conformation; and the second state of the mixture corresponds to the nanomaterial electrolyte being predominantly in an opposite conformation to the first state, i.e., if the nanomaterial electrolyte is predominantly in a flat two-dimensional conformation in the first state, it is predominantly in a scrolled one-dimensional conformation in the second state, or vice versa; The nanomaterial electrolyte comprises a modified two-dimensional nanomaterial having a surface; the surface is modified with a plurality of functional groups selected from one or more of the group consisting of imine, sulfonic acid, sulfonamide, amine, hydroxyl, carboxylic acid, thiol, and amide on the surface of the modified two-dimensional nanomaterial; The nanomaterial electrolyte can reversibly adopt a flat two-dimensional conformation or a scrolled one-dimensional conformation in response to changes in its surrounding environment; the change in the surrounding environment is due to a change in one or more of pH, ionic strength, and sonication in the surrounding environment; and The amount of said functional groups is greater than that present in the unmodified form of the same two-dimensional nanomaterial. method.
2. 2. The method of claim 1, The method comprises: (c) subjecting the mixture to one or more of the following changes in the surrounding environment: pH, ionic strength, and sonication to return the mixture to the first state, i.e., to return the nanomaterial electrolyte to its morphology in the first state; Also includes method
3. 3. The method according to claim 1 or 2, The changes in the surrounding environment include the following changes: (a) one or more of salt concentration, pH, ionic strength, and sonication in said surrounding environment; (b) one or more of the pH, ionic strength, and sonication of said ambient environment; or (c) one or both of pH and sonication of said ambient environment; is method.
4. The method according to any one of claims 1 to 3, The modified two-dimensional nanomaterial is selected from one or more of graphene, graphene oxide, reduced graphene oxide, hexagonal boron nitride, and transition metal dichalcogenides; wherein the modified two-dimensional nanomaterial optionally comprises: (a) selected from one or more of graphene and graphene oxide; and / or (b) a transition metal dichalcogenide; The transition metal dichalcogenide may be molybdenum disulfide; and / or (c) is a single layer or is formed from 2 to 5 layers; May be; method.
5. The method according to any one of claims 1 to 4, The functional groups are selected from one or more of the group consisting of: (a) amines, hydroxyls, carboxylic acids, thiols, and amides; or (b) amino, hydroxyl, carboxylic acid, and thiol; or (c) hydroxyls, carboxylic acids, and thiols; or (d) a carboxylic acid and a thiol; or (e) amines and imines; or (f) hydroxyl, carboxylic acid, and sulfonic acid; or (g) thiols and sulfonamides; or (h) amines and carboxylic acids; method.
6. A method according to any one of claims 1 to 5, comprising: (a) the nanomaterial electrolyte is further coated with a material selected from one or more of the group consisting of polymers, proteins, carbohydrates, and nanoparticles; The nanomaterial electrolyte may be coated with a material selected from one or more of the group consisting of poly(ethylene glycol) (PEG), poly(methyl methacrylate) (PMMA), proteins, silica, dextran, gold nanoparticles, gold nanorods, silver nanoparticles, platinum nanoparticles, titanium dioxide, and silica nanoparticles; and / or (b) the nanomaterial electrolyte further comprises fluorescent groups covalently attached to the surface; method.
7. 1. A nanomaterial electrolyte comprising: The nanomaterial electrolyte comprises a modified two-dimensional nanomaterial having a surface; The surface is modified with a plurality of functional groups selected from one or more of the group consisting of imine, sulfonic acid, sulfonamide, amine, hydroxyl, carboxylic acid, thiol, and amide on the surface of the modified two-dimensional nanomaterial; The nanomaterial electrolyte can reversibly adopt a flat two-dimensional conformation or a scrolled one-dimensional conformation in response to changes in its surrounding environment; the change in the surrounding environment is due to a change in one or more of pH, ionic strength, and sonication in the surrounding environment; and The amount of said functional groups is greater than that present in the unmodified form of the same two-dimensional nanomaterial. Nanomaterial electrolytes.
8. 8. The nanomaterial electrolyte according to claim 7, The nanomaterial electrolyte is in an aqueous surrounding environment. Nanomaterial electrolytes.
9. The nanomaterial electrolyte according to claim 7 or 8, The changes in the surrounding environment include the following changes: (a) one or more of salt concentration, pH, ionic strength, and sonication in said surrounding environment; or (a) one or more of the pH, ionic strength, and sonication of said ambient environment; or (b) one or both of pH and sonication of said ambient environment; Caused by Nanomaterial electrolytes.
10. The nanomaterial electrolyte according to any one of claims 7 to 9, the modified two-dimensional nanomaterial is selected from one or more of graphene, graphene oxide, reduced graphene oxide, hexagonal boron nitride, and transition metal dichalcogenides; where, optionally: (a) the modified two-dimensional nanomaterial is selected from one or more of graphene and graphene oxide; and / or (b) the modified two-dimensional nanomaterial is a transition metal dichalcogenide; The transition metal dichalcogenide may be molybdenum disulfide; and / or (c) the modified two-dimensional nanomaterial is a single layer or is formed from 2-5 layers; May be; Nanomaterial electrolytes.
11. The nanomaterial electrolyte according to any one of claims 7 to 10, The functional groups are selected from one or more of the group consisting of: (a) amines, hydroxyls, carboxylic acids, thiols, and amides; or (b) amino, hydroxyl, carboxylic acid, and thiol; or (c) hydroxyls, carboxylic acids, and thiols; or (d) a carboxylic acid and a thiol; or (e) amines and imines; (f) hydroxyl, carboxylic acid, and sulfonic acid; or (g) thiols and sulfonamides; or (h) amines and carboxylic acids; Nanomaterial electrolytes.
12. A nanomaterial electrolyte according to any one of claims 7 to 11, comprising: (a) the nanomaterial electrolyte is further coated with a material selected from one or more of the group consisting of polymers, proteins, carbohydrates, and nanoparticles; The nanomaterial electrolyte may be coated with a material selected from one or more of the group consisting of poly(ethylene glycol) (PEG), poly(methyl methacrylate) (PMMA), proteins, silica, dextran, gold nanoparticles, gold nanorods, silver nanoparticles, platinum nanoparticles, titanium dioxide, and silica nanoparticles; and / or (b) the nanomaterial electrolyte further comprises fluorescent groups covalently attached to the surface; Nanomaterial electrolytes.
13. A method for forming the nanomaterial electrolyte according to any one of claims 7 to 12, comprising the steps of: The method includes the following steps: (i) providing an unmodified two-dimensional nanomaterial; and (ii) reacting said unmodified two-dimensional nanomaterial with one or more functionalizing reagents in the presence of a solvent to provide a nanomaterial electrolyte; Includes method.
14. 14. The method according to claim 13, further comprising: The unmodified two-dimensional nanomaterial is selected from one or more of graphene, graphene oxide, reduced graphene oxide, hexagonal boron nitride, and transition metal dichalcogenides; wherein the unmodified two-dimensional nanomaterial optionally comprises: (a) selected from one or more of graphene, graphene oxide, and transition metal dichalcogenides; The transition metal dichalcogenide may be molybdenum disulfide; and / or (b) selected from one or more of graphene and graphene oxide; and / or (c) a transition metal dichalcogenide; The transition metal dichalcogenide may be molybdenum disulfide; and / or (d) is a single layer or is formed from 2 to 5 layers; May be; method.
15. 15. The method according to claim 13 or claim 14, the one or more functionalizing reagents are selected from compounds that impart one or more functional groups to the nanomaterial electrolyte, such as imines, sulfonic acids, sulfonamides, or more specifically, amines, hydroxyls, carboxylic acids, thiols, and amides; The one or more functionalizing reagents may be selected from compounds that impart to the nanomaterial electrolyte one or more functional groups selected from one or more of the group consisting of: (a) amines, hydroxyls, carboxylic acids, thiols, and amides; or (b) amino, hydroxyl, carboxylic acid, and thiol; or (b) hydroxyls, carboxylic acids, and thiols; or (c) a carboxylic acid and a thiol; or (d) amines and imines; or (e) hydroxyl, carboxylic acid, and sulfonic acid; or (f) thiols and sulfonamides; or (g) amines and carboxylic acids; method.
16. 16. The method of claim 15, further comprising: the one or more functionalizing reagents are selected from one or more of the group consisting of thioamines, difunctional sulfonic acids, aminosilanes, carboxylsilanes, thiolsilanes, difunctional amines, polyfunctional amines, azide compounds, dienophiles, thioacids, and haloacetamides; where, optionally: (a) the one or more functionalizing reagents are selected from the group consisting of sulfanilic acid, (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-aercaptopropyl)methyldimethoxysilane, ethylenediamine (EA), 1,6-hexanediamine (HA), triethylenetetramine (TETA), azido-OH, azido-COOH, azido-NH 2 , azido polymers, lipoic acid (LA), lipoic acid derivatives, mercaptopropionic acid (MPA), thioglycerol (TG), cysteine, methyl iodide, and iodoacetamide; or (b) the one or more functionalizing reagents may be selected from one or more of the group consisting of (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-mercaptopropyl)methyldimethoxysilane, ethylenediamine (EA), 1,6-hexanediamine (HA), triethylenetetramine (TETA), 5-azidopentanoic acid, azido-dPEG-amine, azido-dPEG-acid, 3-azido-1-propanol, 3-azido-1-propanamine, azomethine ylide, lipoic acid (LA), lipoic acid derivatives, mercaptopropionic acid (MPA), thioglycerol (TG), cysteine, methyl iodide, and iodoacetamide; method.
17. The method according to any one of claims 13 to 16, One or more of the following may apply: (a) step (ii) in claim 13 is carried out using an activating molecule; The activating molecules are 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), N-hydroxysuccinimide (NHS), and thionyl chloride, SOCl. 2 may be selected from the group consisting of: (b) the reaction product of step (ii) in claim 13 is subjected to reduction in step (iii), the reducing step comprising reacting the reaction product of step (ii) with a reducing agent in the presence of a solvent; The reduction may be carried out using a reducing agent selected from one or more of the group consisting of ascorbic acid, hydrazine, and sodium borohydride; and (c) the reaction product of step (ii) in claim 13 is reacted with a fluorescent agent in step (iv) in the presence of a solvent; The fluorescent agent may be fluorescin isothiocyanate isomer type I, and the reaction product of step (ii) may contain a thiol functional group; method.
18. 1. A drug delivery device comprising: The drug delivery device comprises: A nanomaterial electrolyte according to any one of claims 7 to 12; and a drug bound to the surface of said nanomaterial electrolyte; Including; The nanomaterial electrolyte is provided in a scrolled one-dimensional conformation such that the drug is encapsulated within the scrolled one-dimensional conformation and released when the nanomaterial electrolyte adopts a flat two-dimensional conformation upon exposure to an acidic or basic environment; Drug delivery devices.